Children color research for application and development of children multimedia courseware / Ahmad Nabil Abd Karim - Abd Karim, Ahmad Nabil (2006)
Education system changes from time to time and at present time it is changing ftxjm the conventional or traditional way of teaching to a more high tech and interesting method. One of these methods is interactive learning. It helps students to more understand the lesson that is being taught through a multimedia system. However in order to design an effective interactive multimedia system there are many aspects, that must be taken account for. One of the aspects is color that is used or applied in the multimedia interface. This is very important, namely from the view of children. Children need an interesting interface to look at, in order to attract their attention. Therefore a research is conducted, using scientific method to find out the colors that children prefer most. These scientific consists of steps problem identification, making hypotheses, research reviews, develop method to achieved project objectives, analyzing the results and conclusion of the result. This color or data that is obtained can then be use for future children multimedia courseware. Therefore hopefully through this research in the future, it will provide children with a more interesting multimedia system and eventually inspire them to learn.